Effect of Vit E, potassium, and alcohol-fermented feed supplementation before transport on body weight, carcass characteristics, and meat color of Hanwoo Steers - Son, Gi Hwal; Park, Byung Ki; Li, Xiang Zi; Choi, Byoung Yang; Shin, Jong Suh (Revista Colombiana de Ciencias Pecuarias, 2024)
Background: During transport of cattle, not only does weight loss occur due to transport stress, but meat quality also deteriorates due to changes in meat color. Hence, stress generated during transportation causes economic loss for livestock farms. Objective: To investigate the effect of vitamin E, potassium, and alcohol-fermented feed supplementation before transport on body weight, carcass characteristics, and meat color of Hanwoo steers. Methods: Forty steers were divided into four treatment groups, with 10 cattle per treatment in two pens. (1) Vitamin E was fed at 500 IU/head/day. (2) An alcohol-fermented feed was fed at 1.58 kg/head/day for six months prior to transport. (3) Potassium at 1.45% of daily feed amount was fed orally one day before transport and (4) the control group. Transportation loss, carcass characteristics, and surface meat color were measured and data were analyzed by GLM (Generalized Linear Model) and Duncan's Multiple Range test using SAS (V.8.01; 2000) package. Results: Weight loss due to transport stress was lower in the treatment groups than in the control, especially with potassium treatment. Meat color, redness, clarity, and hue angle were significantly improved (add the p-value) in treatments compared to the control but fat color, marbling score, back fat thickness, carcass percentage, and meat production index were not different among treatments. Conclusion: Supplementation of alcohol-fermented feed, potassium, and vitamin E before transportation improves productivity by preventing loss in body weight and deterioration of the meat color due to transportation stress.